The Relationship between Work Motivation and Job Satisfaction of Barista Training Participants at the Padang City Job Training Center - Arifqi, Muhammad; Irmawita, Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background to this study arises from attention to the increasingly rapid growth of the coffee and cafe industry today. Along with this, the demand for quality coffee drinks is also increasing. Baristas play an important role in providing customers with a quality coffee experience, and barista training is an important factor in developing the necessary skills. Padang City Workout Hall as a recognized training institution has an important role in scoring qualified baristas. However, in order to guarantee the effectiveness of training, not only technical skills must be taken into account, but also the motivation and job satisfaction of trainees. High motivation can encourage participants to reach their best potential in learning, while high job satisfaction can have a positive impact on participant retention and training quality. This type of research is quantitative research, with a correlational approach. Correlational research is a study that researchers conduct to observe the degree of relationship between two or more variables, without modification, addition or engineering with existing data. The motivation of trainees who feel motivated to attend training can increase job satisfaction. If they see the value and benefits of such training, they will most likely be satisfied with their decision to attend the training. Trainees who are always present, actively ask questions, and involve themselves fully in each training session tend to feel more satisfied. Good attendance can reflect a commitment to training and a desire to maximize its benefits. Environmental factors, such as training facilities, classroom atmosphere, and the relationship between trainees and instructors, can also affect job satisfaction. There is a significant relationship between work motivation and job satisfaction of barista trainees in Padang City, so motivation strongly influences satisfaction in carrying out training. Keywords: Work motivation, job satisfaction, training